Comparative mitochondrial phylogeography of water frogs (Ranidae: Pelophylax spp.) from the southwestern Balkans - Petr Papežík; Peter Mikulíček; Michal Benovics; Monika Balogová; Lukáš Choleva; Marie Doležálková-Kaštánková; Petros Lymberakis; Edvárd Mizsei; Simona Papežíková; Nikos Poulakakis; Enerit Saçdanaku; Márton Szabolcs; et al. (Vertebrate Zoology, 2023)
The genus Pelophylax (water frogs) includes relatively common, widely distributed, and even invasive species, but also endemic taxa with small ranges and limited knowledge concerning their ecology and evolution. Among poorly studied species belong endemics of the southwestern Balkans, namely Pelophylax shqipericus, P. epeiroticus and P. kurtmuelleri. In this study, we focused on the genetic variability of these species aiming to reveal their phylogeographic patterns and Quaternary history. We used 1,088 published and newly obtained sequences of the mitochondrial ND2 gene and a variety of analyses, including molecular phylogenetics and dating, historical demography, and species distribution modeling (SDM). We revelated the existence of two mitochondrial lineages within P. epeiroticus and P. shqipericus that diverged at ~ 0.9 Mya and ~ 0.8 Mya, respectively. Contrarily, no deeply diverged lineages were found in P. kurtmuelleri. Pelophylax kurtmuelleri also shows a close phylogenetic relationship with widely distributed P. ridibundus, suggesting that both represent one evolutionary clade called here P. ridibundus/kurtmuelleri. The estimated split between both lineages in the clade P. ridibundus/kurtmuelleri date back to ~ 0.6 Mya. The divergence between the ridibundus and kurtmuelleri lineages on the ND2 gene is thus lower than the divergence between the two lineages found in P. epeiroticus and P. shqipericus. According to haplotype networks, demographic analyses, and SDM, endemic water frogs survived the last glacial maximum (LGM) in Balkan microrefugia, and their distribution has not changed significantly or even retracted since the LGM. Haplotypes of the kurtmuelleri lineage were also found in northern parts of Europe, where haplotype diversity is however much lower than in the Balkans, suggesting the possible hypothesis of their postglacial expansion to the north.